SP0009 Case Presentation: Igg4 Related Disease. (10th June 2014) - Reis, P.
Abstract : IgG4-related disease is a fibroinflammatory disorder of unknown etiology that can affect any organs. It is characterized by diffuse or localized infiltration of the involved tissue by IgG4- positive plasma cells associated with lymphoplasmacellular inflammation, storiform fibrosis and obliterative phlebitis. Elevated serum concentrations of IgG4 are present in many patients. Here we report the case of a patient with multi organ involvement due to IgG4-related disease. A 71-year-old Caucasian man presented with sialadenitis of the left submandibulary gland. Biopsy of the gland revealed distinct chronic sclerosis as well as lymphoplasmacytic infiltration with more than 100 IgG4-positive plasma cells per high power field. The patient developed progressive dyspnea and a chest CT scan showed thickening of the interlobular septum and alveolar walls as well as bilateral infiltrates and ground glass opacities. Serum concentration of IgG4 was 1050mg/dl (reference value 5 - 125mg/dl). The patient was initially treated with steroids with substantial clinical improvement and decrease of IgG4 serum levels. As the steroids were tapered, the patient developed cholangitis and pancreatitis. Another course of glucocorticoid therapy and adjunctive Rituximab therapy resulted in full clinical remission. Disclosure of Interest: None declared DOI: 10.1136/annrheumdis-2014-eular.6187